Analysis of the Problems of Implementing Sekolah Penggerak Program in Improving Teacher Quality in Junior High School - Rukmaini, Rukmaini; Nurzen, M; Zebua, Ali Marzuki (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the problems in implementing the Sekolah Penggerak program located at SMP Negeri 13 Kerinci in the 2024/2025 school year, with the samples used are teachers and principals. This research uses a qualitative approach with a case study method to analyze the challenges in implementing the Sekolah Penggerak program. Data were collected through in-depth interviews with teachers and principals and observations of teaching activities and program implementation at school. Data analysis was done thematically to identify the main obstacles teachers face and explore strategies that can be applied to increase the program's effectiveness in improving teaching quality. The results show that although the program has great potential to improve the quality of education, various challenges arise, such as technology adaptation among senior teachers and traditional learning methods. A more intensive approach is needed to overcome these obstacles, such as more focused training, personal mentoring, and adequate resource support. This research implies the need for active involvement of all parties, including school principals and education offices, in supporting the program's success. The program requires technical and school culture changes that support innovative and collaborative learning to improve education quality sustainably.